Validity and Practicality: Development of an Interactive Flipbook to Enhance Students Knowledge and Digital Literacy - Hadi, Achmad Syaiful; Rahayu, Sri Endarti; Saputro, Budiyono (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The 21st century increases competitiveness by requiring students to have various skills. Technology and learning media are very important to support the learning process. However, without new innovations in the use of this learning media, students will not achieve learning goals and master the skills needed. The purpose of this study is to design and develop interactive learning media in the form of flipbooks to improve students understanding and digital literacy on the classification of living things, Plantae sub-material, Angiosperm sub-division, especially about the types of medicinal plants used by the Betawi Ciracas people. It also aims to provide new knowledge with interactive digital learning media, so that it can be used while learning. The results of this research are in the form of an interactive flipbook named